Effects of Erythropoietin on Cardiac Remodeling After Myocardial Infarction - Nishiya Daisuke; Omura Takashi; Shimada Kenei; Matsumoto Ryo; Kusuyama Takanori; Enomoto Soichiro; Iwao Hiroshi; Takeuchi Kazuhide; Yoshikawa Junichi; Yoshiyama Minoru (Elsevier, 2006)
Abstract.: Erythropoietin (EPO) has been suggested to have a cardioprotective effect against ischemia. The purpose of this study was to examine the effects of EPO on cardiac remodeling after myocardial infarction (MI). MI was induced by ligation of the coronary artery in Wistar rats. The rats with MI were randomly divided into untreated MI and two EPO-treated MI groups. EPO was administered subcutaneously by injection once a day for 4 days after MI at 5000 U/kg or 3 times a week for 4 weeks at 1000 U/kg. Five days after MI, EPO prevented the increase in activated caspase 3, matrix metalloproteinase-2, and transcriptional activation of activator protein-1 in non-infarcted myocardium. Four weeks after MI, left ventricular weight, left ventricular end-diastolic pressure, and left ventricular dimension were increased, and ejection fraction and E wave deceleration time were decreased. EPO significantly attenuated this ventricular remodeling and systolic and diastolic dysfunction. In addition, EPO significantly attenuated the interstitial fibrosis and remodeling-related gene expression in non-infarcted myocardium. Furthermore, EPO significantly enhanced angiogenesis and reduced apoptotic cell death in peri-infarcted myocardium. In conclusion, when administered after MI, EPO prevents cardiac remodeling and improves ventricular function with enhanced angiogenesis and reduced apoptosis. Keywords:: myocardial infarction, cardiac remodeling, erythropoietin, angiogenesis, apoptosis